Meningkatkan Keterampilan Motorik Halus Anak Melalui Kegiatan Menganyam Pada Kelompok B Di TK Pelita Hati - Nabila Safitri; Yenda Puspita; Amin Yusi Nur Sa’ida; Musnar Indra Daulay; Moh Fauziddin (JURNAL ARMADA PENDIDIKAN, 2025)
This research is motivated by children's fine motor skills that have not developed optimally. Therefore, it is necessary to improve them with weaving activities using various media. The problem in this study is that coloring is still stiff, like moving fingers, so the coloring results tend to be untidy; children's cutting activities have not been able to cut according to the pattern in the implementation of fine motor learning. This study aims to determine the fine motor skills of children in group B of Pelita Hati Pulau Payung Kindergarten through weaving activities. The subjects were 15 children (6 boys and 9 girls). This research used the Classroom Action Research method. Data collection techniques used were observation and documentation. Data analysis techniques used the formula P = (F/N) x 100% to calculate the percentage of children's fine motor skills. The results showed that the percentage of children's fine motor skills from the initial condition was 33%. In cycle I, it increased to 51%, and in cycle II, it increased to 79.8%. This proves that the weaving method can improve children's fine motor skills at Pelita Hati Pulau Payung Kindergarten.